2023
DOI: 10.3389/fneur.2023.1097473
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of disease-modifying effect of drugs in experimental epilepsy

Abstract: ObjectiveEpilepsy affects ~50 million people worldwide causing significant medical, financial, and sociologic concerns for affected patients and their families. To date, treatment of epilepsy is primarily symptomatic management because few effective preventative or disease-modifying interventions exist. However, recent research has identified neurobiological mechanisms of epileptogenesis, providing new pharmacologic targets to investigate. The current scientific evidence remains scattered across multiple studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Despite extensive study, however, mTOR inhibitors, such as rapamycin, sirolimus, and everolimus have demonstrated limited clinical benefit due to inconsistent results and significant side effects due to multiple downstream effects ( Karalis and Bateup, 2021 ). Many other compounds targeting various mechanistic targets remain in the preclinical phase ( Ots et al, 2023 ). For example, the soluble epoxide hydrolase receptor, through inhibition by TPPU pretreatment, was found to rescue dendritic spine loss and attenuate seizure severity ( Peng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive study, however, mTOR inhibitors, such as rapamycin, sirolimus, and everolimus have demonstrated limited clinical benefit due to inconsistent results and significant side effects due to multiple downstream effects ( Karalis and Bateup, 2021 ). Many other compounds targeting various mechanistic targets remain in the preclinical phase ( Ots et al, 2023 ). For example, the soluble epoxide hydrolase receptor, through inhibition by TPPU pretreatment, was found to rescue dendritic spine loss and attenuate seizure severity ( Peng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%